Peran Taman Pendidikan Al Quran (TPA) Dalam Pembentukan Karakter Islami Di Tpa Darussalam Desa Kagokan, Kecamatan Gatak - Mumtazah, Muti’ah Nuha; Rohmatic, Zahra Ar; Rahmadani, Eka; Pure, Auliah Azizah P.; Abdulloh, Fadhil (CV. SINAR HOWUHOWU, 2025)
In today’s era of globalization, the rapid development of information and technology significantly impacts society, including children. This study aims to describe the role of Taman Pendidikan Al-Qur’an (TPA) Darussalam in shaping Islamic character among children in Kagokan Village, Gatak District. The background of this research lies in the concern over the erosion of manners and moral values among children in the digital age. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and documentation involving teachers and students. The findings reveal that TPA Darussalam not only teaches Qur’anic literacy but also instills Islamic values such as honesty, responsibility, discipline, and courtesy through a personal and engaging learning approach. The character education strategies implemented include habituation, role modeling, and programs such as “One Day One Character.” Positive impacts are evident in the behavioral changes of students who become more religious and well-mannered. This study highlights the crucial role of non-formal education institutions in nurturing Islamic character from an early age.